Pulmonary events in ICU patients with hyperoxia: is it possible to relate arterial partial pressure of oxygen to coded diseases?$dA retrospective analysis - Stroh, Lubov; Nurjadi, Dennis; Uhle, Florian; Bruckner, Thomas; Kalenka, Armin; Weigand, Markus A.; Fiedler-Kalenka, Mascha (Medicina intensiva, 2024)
Objective - Oxygen has been used liberally in ICUs for a long time to prevent hypoxia in ICU- patients. Current evidence suggests that paO2 >300 mmHg should be avoided, it remains uncertain whether an “optimal level” exists. We investigated how “mild” hyperoxia influences diseases and in-hospital mortality. - Design - This is a retrospective study. - Setting - 112 mechanically ventilated ICU-patients were enrolled. - Patients or participants - 112 ventilated patients were included and categorized into two groups based on the median paO2 values measured in initial 24 h of mechanical ventilation: normoxia group (paO2 ≤ 100 mmHg, n = 43) and hyperoxia group patients (paO2 > 100 mmHg, n = 69). - Interventions - No interventions were performed. - Main variables of interest - The primary outcome was the incidence of pulmonary events, the secondary outcomes included the incidence of other new organ dysfunctions and in-hospital mortality. - Results - The baseline characteristics, such as age, body mass index, lactate levels, and severity of disease scores, were similar in both groups. There were no statistically significant differences in the incidence of pulmonary events, infections, and new organ dysfunctions between the groups. 27 out of 69 patients (39.1%) in the “mild” hyperoxia group and 12 out of 43 patients (27.9%) in the normoxia group died during their ICU or hospital stay (p = 0.54). The mean APACHE Score was 29.4 (SD 7.9) in the normoxia group and 30.0 (SD 6.7) in the hyperoxia group (p = 0.62). - Conclusions - We found no differences in pulmonary events, other coded diseases, and in-hospital mortality between both groups. It remains still unclear what the "best oxygen regime" is for intensive care patients. - Resumen - Objetivo - El oxígeno durante mucho tiempo se ha utilizado generosamente en la UCI para prevenir la hipoxia de los pacientes. Las pruebas actuales sugieren que debe evitarse una paO2 >300 mmHg, pero aún no se sabe con certeza si existe un "nivel óptimo". Se investigó cómo la hiperoxia "leve" influye en la morbi-mortalidad intrahospitalaria. - Diseño - Se trata de un estudio retrospectivo. - Ámbito - Se incluyeron 112 pacientes de UCI con ventilación mecánica. - Pacientes o participantes - Los 112 pacientes se clasificaron en dos grupos en función de los valores medios de paO2, medidos durante las primeras 24 horas de la ventilación mecánica: pacientes del grupo de normoxia (paO2 ≤ 100 mmHg, n = 43) y pacientes del grupo de hiperoxia (paO2 > 100 mmHg, n = 69). - Intervenciones - No se realizaron intervenciones. - Principales variables de interés - El resultado primario fue la incidencia de episodios pulmonares, los resultados secundarios incluyeron la incidencia de otras disfunciones orgánicas nuevas y la mortalidad intrahospitalaria. - Resultados - Las características basales, como la edad, el índice de masa corporal, los niveles de lactato y las puntuaciones de gravedad de la enfermedad, fueron similares en ambos grupos. No hubo diferencias estadísticamente significativas en la incidencia de episodios pulmonares, infecciones y nuevas disfunciones orgánicas entre los grupos. Pudo observarse que 27 de 69 pacientes (39,1%) del grupo de hiperoxia "leve" y 12 de 43 pacientes (27,9%) del grupo de normoxia fallecieron durante su estancia en la UCI o en el hospital (p = 0,54). La puntuación APACHE media fue de 29,4 (DE 7,9) en el grupo de normoxia y de 30,0 (DE 6,7) en el grupo de hiperoxia (p = 0,62). - Conclusiones - No encontramos diferencias en episodios pulmonares, otras enfermedades codificadas y mortalidad intrahospitalaria entre ambos grupos. Sigue sin estar claro cuál es el "mejor suministro de oxígeno" para los pacientes de cuidados intensivos.